An assessment of the stressors and ways of coping in Iranian medical sciences students - Niknami, Maryam (Iran J Nurs Midwifery Res, 2015)
BACKGROUND: Several studies have reported that medical sciences students are usually dealing with severe stress. However, no study is available on ways of coping in medical sciences students in Iran. As socio-cultural factors may affect the students’ responses toward stress, this study aimed to investigate the stressors and ways of coping among students of Guilan University of Medical Sciences (GUMS). MATERIALS AND METHODS: A cross-sectional study was conducted on 487 randomly selected students in GUMS in 2012. The student stress scale and Lazarus ways of coping scale were used for data collection. Descriptive statistics were calculated. Also, Chi-square and Fisher's exact tests, Kruskal–Wallis and Mann–Whitney U tests, and logistic regression analysis were utilized for data analysis. cross-sectional study was conducted on 487 randomly selected students in GUMS in 2012. The student stress scale and Lazarus ways of coping scale were used for data collection. Descriptive statistics were calculated. Also, Chi-square and Fisher's exact tests, Kruskal–Wallis and Mann–Whitney U tests, and logistic regression analysis were utilized for data analysis. RESULTS: In the majority of students (61.4%), interpersonal factors were the dominant stressor. Most of the students used problem-focused ways of coping (79.7%). Chi-square test showed a significant relationship between gender and ways of coping (P = 0.03). CONCLUSIONS: Interpersonal sources of stress were the most common stressors among the medical sciences students. Establishing workshops on communication skills and effective counseling system are suggested.